Losses in sugarcane varieties BO 70 and BO 74 due to red rot - V. KUMAR; B. KUMAR, S.P. PANDEY, S. KUMAR, N.B. DWIVEDI (Indian Phytopathology, 2002)
Red rot disease of sugarcane (Colletotrichum falcatum [Glomerella tucumanensis]) is a serious disease in Bihar, India. A field experiment was undertaken during 1995-97 to study the effects of planting red rot infected setts of susceptible varietiesBO 70 and BO 74 on the development of red rot disease, yield attributes and juice quality. Different levels of disease intensity were determined by mixing diseased and healthy canes at different ratios. Results revealed a drastic reduction in sett germinability in response to red rot infection. The crop raised from naturally infected setts had the least germination and the highest red rot incidence, followed by the crop of artificially inoculated setts. The reduction in cane weight, juice content, brix,sucrose content, purity and recovery of jaggery varied according to the levels of red rot infection. It was concluded that both naturally and artificially infected setts may serve as a primary source of red rot infection and cause appreciable losses both in yield and sugar recovery through poor germination, mortality of cane shoots and impaired juice quality.